Caracterização espaço-temporal de áreas da cultura cafeeira infectada por nematóides a partir de imagens multiespectrais - Paula, Paulo Victor Dantas Mendes de (2018)
Coffee is one of the most important crops in the country, the estimate for the Brazilian crop in 2018 is 59.9 million bags benefited, a scenario that is based on productivity. The factors limiting the production of coffee in Brazil and in the world stand out the phytonematoids, the actions of these microorganisms prevent the growth of coffee, making the coffee less productive. The nematodes in the root system of the coffee tree cause nutritional imbalances in the plant that cause variations in the spectral response of the leaf and defines a characteristic spatial configuration. There is a need for an alternative way of monitoring this parasitism. Remote sensing is a technique that makes it possible to obtain diverse information such as: cultivated area, agricultural production, vegetative vigor and offer subsidies for agricultural management. The multispectral images of RapidEye use the Border Red band, which is specific for the monitoring of the photosynthetic activity of the vegetation. The objective of this study was to spectrally characterize the infected coffee tree and to quantify the temporal space growth of areas of the infected coffee crop. The study area is located in the municipality of Monte Carmelo (Minas Gerais), about 48 hectares and is made up of coffee trees that are under advanced development. Through the segmentation where it became possible to discriminate healthy coffee and nematoid infected coffee, it was possible with the vegetation index by normalized difference between red and borderline red, since this spectral range is more sensitive to changes in the internal structure of the plant. Through this study, it was possible to spatially delimit where the reticulum is present in the crop or when it comes to nematodes.